Granular cell tumor presenting as a tongue nodule: Two case reports - Sena Costa, Nivea [UNESP]; Bertini, Fernanda [UNESP]; Carvalho, Yasmin [UNESP]; Almeida, Janete [UNESP]; Rodrigues Cavalcante, Ana [UNESP] (Springer Nature, 2012)
Introduction. Granular cell tumor is an uncommon neoplasm that can occur in any part of the body, including the orofacial region. The tumor is usually benign, but there are reports of cases in which the tumor shows a locally aggressive behavior, malignancy, and distant metastases. The most widely accepted hypothesis is that granular cell tumor arises from the altered metabolism of Schwann cells. The tumor is typically asymptomatic and appears as a nodule that does not exceed 3 cm. Case presentation. In case 1, a 26-year-old Caucasian man was seen at the Oral Medicine out-patient clinic of the São José dos Campos Dental School, Universidade Estadual Paulista, with a 'small blister on the tongue', which he had noted approximately three years ago. The nodule was located on the dorsum of the tongue, measured about 1.5 cm in diameter, and was not tender to palpation. Treatment consisted of an excisional biopsy performed on the basis of the diagnostic hypothesis of granular cell tumor, which was confirmed by microscopic analysis. In case 2, a 31-year-old Caucasian woman attended the out-patient clinic of the São José dos Campos Dental School, Universidade Estadual Paulista, with a five-year history of a 'painful lump on the tongue'. Intra-oral examination revealed the presence of a nodular lesion measuring approximately 0.8 cm in diameter, which was located deep in the submucosa of the right lateral margin of the tongue. Treatment consisted of an excisional biopsy performed on the basis of the differential diagnosis of neurofibroma and granular cell tumor. Microscopic analysis defined the final diagnosis of granular cell tumor. Conclusions: Granular cell tumor is an uncommon tumor that must be carefully diagnosed and treated correctly. © 2012 Sena Costa et al; licensee BioMed Central Ltd.
Keywords: adult; biopsy; case report; differential diagnosis; excision; female; granular cell tumor; histology; human; human tissue; male; microscopy; neurofibroma; priority journal; tongue tumor; tumor diagnosis; tumor growth; tumor localization